Performance Analysis Measured by Key Performance: (Case Study on Siloam Hospitals Bali) - Virnanda, Vika; Santoso, R Tri Priyono Budi; Adinegara, Gusti Ngurah Joko; Junaedi, I Wayan Ruspendi (The Eastasouth Management and Business, 2024)
Humans are the main asset in an organization, so human resources (HR) must be managed and utilized in a balanced and humane manner. A private hospital is a health institution owned by a non-profit and private company whose operational activities are financed through payments for medical services by the patients themselves. Siloam Hospital Bali is located at Jl. Sunset Road No. 818, Kuta, Kec. Kuta, Badung Regency, Bali with a total of 73 employees as respondents. This research aims to determine performance analysis as measured by key performance (financial and profitability, customer satisfaction, internal processes, learning and growth and company performance). The research data is secondary data obtained from Siloam Hospitals Bali. Testing the research hypothesis used SPSS (Statistical Product and Service Solution) analysis techniques. The research results show that financial and profitability (X1), customer satisfaction (X2), internal processes (X3), learning and growth both partially and simultaneously have a positive and significant influence on company performance (Y). It is hoped that in future research other variables that influence company performance can be examined.